Prediction Value of B-ultrasound with Tumor Markers for Malignant Transformation of Mucinous Ovarian Tumors - JI Mengying, LI Yujing, CHEN Xing, DAI Huihua, SUN Ying (Zhongguo quanke yixue, 2023)
Background Mucinous ovarian tumors (MOT) can be divided into three types: benign〔such as mucinous cystadenoma (MCA) 〕, borderline〔such as mucinous borderline tumor (MBT) 〕, and malignant〔such as mucinous cystadenocarcinoma (MC) 〕. It is difficult to differentiate between the types preoperatively, and the final diagnosis depends on surgical pathology. So how to reduce the difficulty in making a preoperative differential diagnosis, and improve the preoperative diagnostic accuracy is particularly important for doctors to make a diagnosis and for patients to choose a treatment option. Objective To explore the high-risk factors associated with malignant transformation of MOT, and to evaluate the predictive value of B-ultrasound combined with tumor markers for malignant transformation of MOT. Methods Retrospective observational study selected surgery-treated 414 women with a histologically confirmed MCA (n=305) , MBT (n=79) and MC (n=30) from the First Affiliated Hospital with Nanjing Medical University during 2010 to 2020. Patients' data, including age, clinical symptoms, sonographic data (tumor size, properties, papilla-shaped protuberance on the cystic wall, blood flow signals, multilocular) and serum tumor markers〔carcinoembryonic antigen (CEA) , carbohydrate antigen 125 (CA125) , carbohydrate antigen 199 (CA199) , carbohydrate antigen 724 (CA724) 〕and D-dimer were collected. Multivariate Logistic regression analysis was used to explore the risk factors of malignant transformation of MOT. The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of B-ultrasound with tumor markers for malignant transformation of MOT, and the area under the curve (AUC) with the corresponding 95%CI were calculated. Results There were statistically significant differences in B-ultrasound manifestations and serological indicators among the three groups (P<0.05) . Maximum diameter of the ovarian tumor≥10 cm〔OR=1.947, 95%CI (1.066, 3.556) , P=0.030〕, solid tumor components〔OR=9.862, 95%CI (4.465, 21.782) , P<0.001〕, papilla-shaped protuberance on the cystic wall〔OR=2.320, 95%CI (1.100, 4.893) , P=0.027〕, blood flow signals〔OR=2.289, 95%CI (1.104, 4.747) , P=0.026〕, multilocular morphology〔OR=5.722, 95%CI (3.034, 10.789) , P<0.001〕, CA125≥35.0 U/mL〔OR=4.307, 95%CI (1.963, 9.452) , P<0.001〕and CA199≥39.0 U/mL〔OR=2.227, 95%CI (1.030, 4.816) , P=0.042〕were independently associated with increased malignant tendency of MOT. The optimal cut-off value of B-ultrasound with tumor markers〔AUC=0.868, 95%CI (0.912, 0.825) , P<0.001〕in predicting the malignant transformation of MOT was 0.354, with 72.5% sensitivity and 90.8% specificity. Conclusion It is need to consider the possibility of malignant transformation of MOT when a patient is found with an ovarian tumor with maximum diameter ≥10 cm with solid components, papilla-shaped protuberance on the cystic wall, blood flow signals, and multilocular morphology, as well as serum CA125≥35.0 U/mL and CAl99≥39.0 U/mL. B-ultrasound with tumor markers may partially predict the malignant transformation of MOT.